Application of firefly algorithm for congestion management problem in the deregulated electricity market. (2018) - Basha, A. Ahamed Jeelani; Anitha, M.; Elanchezhian, E.B.
In the deregulation of electricity market, the transmission congestion management (CM) has become extremely important in order to ensure security and reliability of the system. This paper proposes a method to manage congestion by optimal rescheduling of the active powers of generators based on firefly algorithm (FA). However, all generators in the system need not take part in CM. Thus, in this article, generators are selected based on the magnitude of generator sensitivities to the congested line. In this paper, the proposed FA is tested on standard IEEE 30 bus, 118 bus systems and a practical Indian utility 62 bus system for the solution of CM problem. The results of these test systems provide minimum rescheduling cost and are compared with that of CPSO, PSO-TVIW, PSO-TVAC, VEPSO and PSO-ITVAC methods. Results prove that FA is indeed capable of getting a high quality solution for the CM problem.